DEVELOPING STUDENTS’ INDEPENDENT LEARNING COMPETENCIES IN AN ARTIFICIAL INTELLIGENCE-BASED DIGITAL EDUCATIONAL ENVIRONMENT: A METHODOLOGICAL APPROACH (Eureka Journal of Education & Learning Technologies, 2026)
This article discusses the methodology for developing students’ independent learning competencies in an artificial intelligence-based digital educational environment. It analyzes the role of AI technologies in supporting personalized learning and self-regulated learning skills.
Keywords: artificial intelligence, digital education, independent learning, competency, adaptive learning, educational technology